Microbial Allies or Adversaries? The Genotype-Dependent Impact of Inoculation on Silver Birch - Greta Striganavičiūtė; Dorotėja Vaitiekūnaitė; Milana Šilanskienė; Vaida Sirgedaitė-Šėžienė (Plants)
Microbial inoculation plays a crucial role in shaping plant physiological and biochemical responses, influencing growth, secondary metabolism, and stress-related markers. This study investigates the effects of PAH-degrading microorganisms (Pseudomonas putida, Sphingobium yanoikuyae, and Rhodotorula sphaerocarpa) on the growth, secondary metabolism, photosynthetic pigment, and stress-related biochemical markers of silver birch (Betula pendula Roth) seedlings from two half-sib families grown hydroponically. Results demonstrate family-dependent variations in the response to microbial treatments. In family 73, the growth of both shoots and roots was inhibited by certain microbial treatments, along with a decrease in key biochemical markers such as phenolic content and carotenoids. Conversely, family 86 showed no growth inhibition and exhibited improvements in some biochemical markers, including flavonoids and chlorophyll. Stress indicators, such as malondialdehyde (MDA) and soluble sugars, displayed contrasting patterns between families, with increased MDA observed in family 73 under certain microbial treatments. In contrast, family 86 did not exhibit an increase in MDA, suggesting differences in stress mitigation. Soluble sugars were generally reduced in family 73. Antioxidant enzyme activity further highlighted these family-specific responses, with variations in enzymes like ascorbate peroxidase (APX) and guaiacol peroxidase (POX) across treatments. Notably, significant interactions between family and microbial treatments were observed for several oxidative stress enzymes, underscoring the role of genotype in shaping the response to microbial stress. These findings highlight the genotype-dependent interactions between microbial inoculation and plant secondary metabolism, providing insights into the role of specifically selected microbial inoculation in stress mitigation and growth regulation.